Antibacterial effects of Lactobacillus acidophilus surface-layer protein in combination with nisin against Staphylococcus aureus. (April 2020) - Wang, Huifang; Niu, Yuhan; Pan, Jie; Li, Qinpei; Lu, Rongrong
Abstract: The objective of this study was to evaluate the bactericidal effects of surface-layer protein (Slp) derived from Lactobacillus acidophilus NCFM, L. acidophilus CGMCC1.1878 in combination with nisin against Staphylococcus aureus and investigate their antibacterial mechanism. Compared with the nisin (MIC, 300 IU/mL) alone treatment, the Slps (50 μ g/mL) + nisin (1/2 MIC, 150 IU/mL) treatment effectively inhibited S. aureus growth and significantly enhanced its cell membrane permeability ( P < 0.05). This combination treatment did not evidently accelerate the leakage of nucleic acids in the cytoplasm, but flow cytometry results showed that the proportion of damaged bacterial cells (including dead and sublethally injured cells) was almost 96.8%, and this combination inactivated intracellular enzymes and decreased the cell membrane potential. Our results showed that Slps enhanced the effect of nisin (1/2 MIC) and reduced the dosage of nisin required for inhibiting S. aureus growth. These results indicate that Slp is a promising combined agent that enhances the antibacterial actions of nisin. The Slps + nisin combination can also be used as a potential antibacterial treatment for food preservation. Highlights: Surface-layer protein (Slp) and nisin presented combined antibacterial effect against S. aureus. Antibacterial mechanism is closely related to the bacterial cell membrane damage. Slp combined with nisin (1/2 MIC, 150 IU/mL) did not accelerate the leakage of nucleic acids. This combination holds great potential as the antibacterial agent. Slp reduced the amount of nisin required for inhibiting S. aureus growth.